2020
DOI: 10.1002/ddr.21650
|View full text |Cite
|
Sign up to set email alerts
|

Trim14 promotes autophagy and chemotherapy resistance of gastric cancer cells by regulating AMPK/mTOR pathway

Abstract: ObjectiveTo study the relationship between TRIM14 expression and chemotherapy resistance of gastric cancer (GC) cells.MethodsThe expression of TRIM14 in 5‐fluorouracil (5‐FU)‐ and oxaliplation (L‐OHP)‐resistant GC tissues and cells were determined by qRT‐PCR and western blotting. PcDNA3.1‐TRIM14 and shRNA‐TRIM14 vector were transfected to 5‐FU‐resistant GC cells (SGC7901/5‐FU), and the proliferation and apoptosis of cells were measured. Animal experiments on 5‐FU‐resistant GC mice were performed to study the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 16 publications
0
17
0
1
Order By: Relevance
“…Generally, RFA treatment can elevate the expression of HSP70 in residual cancer cells located in the transition area, then phosphorylate AKT to activate mTOR signaling, which promotes 4EBP1 and p70S6K phosphorylation, and finally accelerates PDAC growth ( Figure 7D ). Considering other regulators of mTOR signaling, such as YAP and AMPK, 41 an mTOR inhibitor was applied to block this pathway. INK-128, a new mTOR inhibitor, can inhibit both phosphorylation of 4EBP1 and p70S6K while the first generation inhibitors can only inhibit p70S6K.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, RFA treatment can elevate the expression of HSP70 in residual cancer cells located in the transition area, then phosphorylate AKT to activate mTOR signaling, which promotes 4EBP1 and p70S6K phosphorylation, and finally accelerates PDAC growth ( Figure 7D ). Considering other regulators of mTOR signaling, such as YAP and AMPK, 41 an mTOR inhibitor was applied to block this pathway. INK-128, a new mTOR inhibitor, can inhibit both phosphorylation of 4EBP1 and p70S6K while the first generation inhibitors can only inhibit p70S6K.…”
Section: Discussionmentioning
confidence: 99%
“…The regulatory proteins of the AMPK pathway have been shown to induce autophagy and chemoresistance ( Table 1). Xiao et al (2020) have suggested that tripartite motif containing 14 (TRIM14) is significantly up-regulated in 5-FU-and OXAresistant gastric cancer tissues and cell lines. Further studies have shown that TRIM14 can promote autophagy and induce chemoresistance by activating the AMPK/mTOR pathway in vivo and in vitro while silencing TRIM14 provides the opposite effects (Xiao et al, 2020).…”
Section: Regulatory Proteins Inducing Both Autophagy and Chemoresistancementioning
confidence: 99%
“…Xiao et al (2020) have suggested that tripartite motif containing 14 (TRIM14) is significantly up-regulated in 5-FU-and OXAresistant gastric cancer tissues and cell lines. Further studies have shown that TRIM14 can promote autophagy and induce chemoresistance by activating the AMPK/mTOR pathway in vivo and in vitro while silencing TRIM14 provides the opposite effects (Xiao et al, 2020). Pei et al (2018) have found that metadherin (MTDH) expression in gastric cancer tissues is significantly increased and positively correlated with 5-FU resistance.…”
Section: Regulatory Proteins Inducing Both Autophagy and Chemoresistancementioning
confidence: 99%
“…The role of mTOR kinase is also diverse. It integrates various signaling pathways, including AKT/mTOR, activated under the in uence of growth factors and mitogens [Xiao F, 2020]. It is believed that mTOR activation inhibits the development of the self-eating process and is accompanied by protein synthesis processes [Tapia, O.…”
Section: Introductionmentioning
confidence: 99%